Computational insights into the membrane fusion mechanism of SARS-CoV-2 at the cellular level - Jimin Wang; Federica Maschietto; Matthew J. Guberman-Pfeffer; Krystle Reiss; Brandon Allen; Yong Xiong; Elias Lolis; Victor S. Batista (Computational and Structural Biotechnology Journal, 2021)
The membrane fusion mechanism of SARS-CoV-2 offers an attractive target for the development of small molecule antiviral inhibitors. Fusion involves an initial binding of the crown-like trimeric spike glycoproteins of SARS-CoV-2 to the receptor angiotensin II-converting enzyme 2 (ACE2) on the permissive host cellular membrane and a prefusion to post-fusion conversion of the spike trimer. During this conversion, the fusion peptides of the spike trimer are inserted into the host membrane to bring together the host and viral membranes for membrane fusion in highly choreographic events. However, geometric constraints due to interactions with the membranes remain poorly understood. In this study, we build structural models of super-complexes of spike trimer/ACE2 dimers based on the molecular structures of the ACE2/neutral amino acid transporter B(0)AT heterodimer. We determine the conformational constraints due to the membrane geometry on the enzymatic activity of ACE2 and on the viral fusion process. Furthermore, we find that binding three ACE2 dimers per spike trimer is essential to open the central pore as necessary for triggering productive membrane fusion through an elongation of the central stalk. The reported findings thus provide valuable insights for targeting the membrane fusion mechanism for drug design at the molecular level.